2008
DOI: 10.3402/ljm.v3i1.4744
|View full text |Cite
|
Sign up to set email alerts
|

Patterns Of Drug Prescribing In A Hospital In Dubai, United Arab Emirates

Abstract: To determine the pattern of drug prescription by consultants in a private hospital in Dubai, United Arab Emirates, 1190 prescriptions were collected from the hospital's pharmacy over 30 days. In total, 2659 drugs were prescribed. The mean number of drugs per encounter was 2.2. Only 4.4% of all drugs prescribed were generic. Polypharmacy was observed in only 7.5% of all encounters. Information about the prescribing physician and the patient was invariably deficient. Name of patient, age, and gender were absent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
7
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 3 publications
3
42
7
1
Order By: Relevance
“…[47][48][49][50] Compared to multivitamin prescription of our study (37.8%) other studies in the region report varying frequencies from 5.9% to 50%. 48,49,[51][52][53] Most of the prescribed drugs were administered orally (12% capsule, 80% tablet form) which was found to be similar as previous study in 2015 where 855 prescriptions were evaluated from SRTR Government Medical, Maharashtra, India. 54 In our present study most of the drugs (92%) were prescribed by brand name which coincides with the report from the survey conducted by previous study.…”
Section: Discussionsupporting
confidence: 54%
“…[47][48][49][50] Compared to multivitamin prescription of our study (37.8%) other studies in the region report varying frequencies from 5.9% to 50%. 48,49,[51][52][53] Most of the prescribed drugs were administered orally (12% capsule, 80% tablet form) which was found to be similar as previous study in 2015 where 855 prescriptions were evaluated from SRTR Government Medical, Maharashtra, India. 54 In our present study most of the drugs (92%) were prescribed by brand name which coincides with the report from the survey conducted by previous study.…”
Section: Discussionsupporting
confidence: 54%
“…13 In similar studies conducted, the antibiotic prescription is remarkably less than that reported in Iran (61.9%) 18 and high than that reported in Nepal (28.3%) 19 . According to WHO, 15-25% of antibiotics encountered is expectable in the countries where an infectious disease is more prevalent.…”
Section: Discussionmentioning
confidence: 79%
“…12 It also showed that more than 3/4 th of the patients (76.33%) were given three or more drugs. Since, WHO has recommended that average number of drugs per prescription should be 2.0, 13 so the results of the study reflect polypharmacy which may lead to adverse drug reactions, increase the risk of drug interactions, dispensing errors, medication errors, decrease adherence to drug regimens and unnecessary drug expenses.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the percentage of encounters with an antibiotic prescription was 50% which is comparable with the results of Norway (48%). 9 In similar studies conducted, the antibiotic prescription is remarkably less than that reported in Iran (61.9%) 14 and high than that reported in Nepal (28.3%) 15 .…”
Section: Discussionmentioning
confidence: 79%
“…8 It also showed that more than 3/4 th of the patients (76.33%) were given three or more drugs. Since, WHO has recommended that average number of drugs per prescription should be 2.0, 9 so the results of the study reflect polypharmacy, which may lead to adverse drug reactions, increase the risk of drug interactions, dispensing errors, medication errors, decrease adherence to drug regimens and unnecessary drug expenses. Use of generic names in prescription eliminate the chance of duplication of drug products and also reduce the cost of the patient.…”
Section: Discussionmentioning
confidence: 99%